Perinatal Trajectories of Maternal Depressive Symptoms in Prospective, Community-Based Cohorts Across 3 Continents - Kee, Michelle Z. L.; Cremaschi, Andrea; Iorio, Maria De; Chen, Helen; Montreuil, Tina; Nguyen, Tuong Vi; Côté, Sylvana M.; O’Donnell, Kieran J.; Giesbrecht, Gerald F.; Letourneau, Nicole; Chan, Shiao Yng; Meaney, Michael J. (American Medical Association, 2023)
Importance Depressive symptoms during pregnancy influence the development and health of the offspring, underscoring the need for timely intervention. However, the course of depressive symptoms across the perinatal period remains unclear, thus complicating screening and referral guidelines. Objective To examine the course and stability of depressive symptoms across the perinatal period in multiple, ethnically diverse independent observational cohorts. Design, Setting, and Participants This cohort study included self-reported depressive symptoms at multiple time points from 7 prospective cohorts spanning 3 continents (United Kingdom: Avon Longitudinal Study of Parents and Children from 1991 to 1995; Canada: Maternal Adversity, Vulnerability and Neurodevelopment from 2003 to 2007; Montreal Antenatal Well-being Study from 2019 to 2022; Alberta Pregnancy Outcomes and Nutrition from 2009 to 2014; and Singapore: Growing Up in Singapore Toward Healthy Outcomes from 2009 to 2013; Singapore Preconception Study of Long-Term Maternal and Child Outcomes from 2015 to 2019; and Mapping Antenatal Maternal Stress from 2019 to 2022). Participants were recruited either during preconception or pregnancy and observed into the postnatal period. All data from each cohort were analyzed from July 2022 to April 2023. Main Outcomes and Measures Self-reported depressive symptoms from pregnancy to 2 years following childbirth using either the Edinburgh Postnatal Depression Scale or the Center for Epidemiological Studies Depression were analyzed independently within each cohort using item response theory (IRT) techniques. K-means clustering was used to identify groups of participants with similar trajectories. Results A total of 11 563 pregnant women (mean [SD] age, 29 [5] years; 569 [4.9%] East Asian women; 304 [2.6%] Southeast Asian women; 10 133 [87.6%] White women) self-reported depressive symptoms from pregnancy to 2 years following childbirth. Analytic methods from Item Response Theory identified 3 groups of mothers based on depressive symptoms: low, mild, and high levels in each of the 7 cohorts. Mothers within and across all cohorts had stable trajectories of maternal depressive symptoms from pregnancy onwards. Mothers with clinical levels of depressive symptoms likewise showed stable trajectories from pregnancy into the postnatal period. Conclusions and Relevance In this study, trajectories of depressive symptoms remained stable from pregnancy across the perinatal period, a finding that conflicts with a continuing emphasis on postpartum or postnatal onset of depression that persists in some health policy guidelines. Interventions and public health initiatives should focus on reducing depressive symptoms during pregnancy in addition to following birth.
Keywords: 32 Ciencias Médicas ::3201 Ciencias clínicas::3201.08 Ginecología; ODS 3 - Salud y bienestar; ODS 5 - Igualdad de género; Depressive Disorders; Psychiatry and Behavioral Health; Reproductive Health; Sexual Health; Women's Health